Electron dynamics of interatomic coulombic decay in quantum dots: singlet initial state - Bande, Annika; Pont, Federico M.; Dolbundalchok, Praphasiri; Gokhberg, Kirill; Cederbaum, Lorenz S. (XVIIIth International Conference on Ultrafast Phenomena 2012, 2013)
In this paper we investigated the interatomic Coulombic decay (ICD) of a resonance singlet state in a model potential for two few-electron semiconductor quantum dots (QDs) by means of electron dynamics. We demonstrate that ICD is the major decay process of the resonance for the singlet wave function and compare the total and partial decay widths as a function of the QD separation with that from our previous study on the corresponding triplet states [1].
Gesehen am 28.10.2020